Dental treatment for children with chronic idiopathic thrombocytopaenic purpura: a report of two cases - B. VAISMAN, A. C. MEDINA & G. RAMIREZ (Paediatric Dentistry, 2004)
Idiopathic thrombocytopaenic purpura (ITP) is the most common acquired bleeding disorder occurring in previously healthy children. The condition is benign and self-limiting, with a high possibility of recovery.